Development and Characterization of Supercooled Polyethylene Naphthalate - Wang, Jian; Li, Hang; Dai, Pan; Chen, Jinnan (Journal of Research Updates in Polymer Science, 2023)
The utilization of undercooled or supercooled polymers presents a promising approach for the creation of single-polymer composites (SPCs), applicable not only to compaction processing but also to extrusion, injection molding, and 3D printing techniques. This study focuses on the development and characterization of supercooled polyethylene naphthalate (PEN) through differential scanning calorimetry (DSC) and rheological measurements. By employing predetermined conditions, a supercooling degree of 50 ˚C for PEN was achieved. The impact of maximum heating temperature, cooling rate, and shear rate on the supercooling degree was examined, revealing that higher supercooling degrees of PEN can be attained by increasing these factors. Additionally, the flow behavior of supercooled polymer melts at various temperatures was analyzed. The supercooling state of PEN exhibited remarkable stability for a minimum duration of half an hour at temperatures exceeding 250 ˚C.